Analysis of 45 candidate genes for disease modifying activity in multiple sclerosis. - Ramagopalan, S; Deluca, G; Morrison, K; Herrera, B; Dyment, D; Lincoln, MR; Orton, S; Chao, M; Degenhardt, A; Pugliatti, M; Sadovnick, A; Sotgiu, S; et al. (2008)
Multiple sclerosis (MS) is a common inflammatory disease of the central nervous system unsurpassed for its variability in disease outcome. As little is conclusively known about MS disease mechanisms, we have selected a variety of candidate genes that may influence the prognosis of the disease based on their function. A cohort of sporadic MS cases, taken from opposite extremes of the putative distribution of long-term outcome using the most stringent clinical criteria to date, was used to determine the role of on MS disease severity. The MS cases selected represent the prognostic best 5 % (benign MS) and worst 5 % (malignant MS) of cases in terms of clinical outcome assessed by the EDSS. Genotyping the two sets of MS patients (112 benign and 51 malignant) and a replication cohort from Sardinia provided no evidence to suggest that the genes selected have any outcome modifying activity, although small effects of these genes cannot be ruled out.